2014
DOI: 10.1089/end.2014.0244
|View full text |Cite
|
Sign up to set email alerts
|

Third Prize: Perineal Robot-Assisted Laparoscopic Radical Prostatectomy: Feasibility Study in the Cadaver Model

Abstract: P-RALP is feasible in the cadaver. Future studies should evaluate the feasibility of lymph node dissection through the same incision, clinical feasibility, and prospective comparisons with standard techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…One limitation of the perineal route is that surgeons are relatively less familiar with the pelvic anatomy, and this may lead to cavernous nerve injury and rectal penetration; also, there is anatomical variation in different individuals, according to the literature [11]. Taking the surgical techniques of Laydner et al [12] and Tuğcu et al [13] as our reference, we were able to identify key anatomical landmarks before placement of the single-site port. The perineal body, or central tendon of the perineum, was first identified after dissection of the subcutaneous tissue.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of the perineal route is that surgeons are relatively less familiar with the pelvic anatomy, and this may lead to cavernous nerve injury and rectal penetration; also, there is anatomical variation in different individuals, according to the literature [11]. Taking the surgical techniques of Laydner et al [12] and Tuğcu et al [13] as our reference, we were able to identify key anatomical landmarks before placement of the single-site port. The perineal body, or central tendon of the perineum, was first identified after dissection of the subcutaneous tissue.…”
Section: Discussionmentioning
confidence: 99%
“…[11] The studies showed that RRP was not superior to RPP in terms of cancer control and continence rates, even though RPP is related with shorter hospital stay, lesser blood loss, lower transfusion rates, lesser amount of analgesic use, and lower postoperative incidence of anastomotic stenosis compared with RRP. [8] In addition, RPP is performed in the extraperitoneal compartment, which also reduces patient discomfort and the possibility of postoperative ileus and provides an early return of appetite and bowel movements. Another advantage of RPP is that it protects the deep dorsal vein complex by retracting it upwards.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the surgeon's vision is restricted which complicates the surgery. r-RPP, defined by Kaouk et al [8,9] , overcomes such difficulties and allows for better maneuverability inside the narrow area with robotic instruments and renders magnified 3D image of the operative field. It seems that robotic surgery is increasing the interest in the perineal approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known from the open perineal approach literature that urine control postoperatively is mostly immediate due to preserved urethra–sphincter complex anatomy [20] , [21] , [22] , [23] , [24] .…”
Section: Surgical Approaches To the Prostatementioning
confidence: 99%